2006
DOI: 10.1097/01.wnp.0000221363.12503.78
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Quantitative EEG Power Associated With Attention-Deficit Hyperactivity Disorder

Abstract: A meta-analysis was performed on quantitative EEG (QEEG) studies that evaluated attention-deficit hyperactivity disorder (ADHD) using the criteria of the DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, 4th edition). The nine eligible studies (N = 1498) observed QEEG traits of a theta power increase and a beta power decrease, summarized in the theta/beta ratio with a pooled effect size of 3.08 (95% confidence interval, 2.90, 3.26) for ADHD versus controls (normal children, adolescents, and adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
10
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 105 publications
14
238
10
5
Order By: Relevance
“…One of the possible reasons for this absence may be found in a recent meta-analysis which suggests that EEG ratios reflect stable trait-like properties and are less sensitive to state-related changes [48]. Clearly, more research is necessary to elucidate the exact contributions of state and trait properties of electric brain activity to the EEG ratios and the assumed relation with emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible reasons for this absence may be found in a recent meta-analysis which suggests that EEG ratios reflect stable trait-like properties and are less sensitive to state-related changes [48]. Clearly, more research is necessary to elucidate the exact contributions of state and trait properties of electric brain activity to the EEG ratios and the assumed relation with emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the following decade, several studies supportive of the link between ADHD and the TBR were published by a handful of research groups, several of which had scientific conflicts of interest. In 2006, Snyder and Hall [28] published a meta-analysis that claimed an effect size of 3.08 for the TBR in ADHD, which they suggested was predictive of sensitivity and specificity of 94%. They subsequently published an empirical study that reported 87% sensitivity, 94% specificity, and 89% overall accuracy for ADHD diagnosis that was relatively invariant according to psychiatric comorbidity, developmental level (child, adolescent), sex, and racial group [29].…”
Section: Diagnostic Biomarkers In Attention Deficit Hyperactivity Dismentioning
confidence: 99%
“…These findings point towards a relation between baseline theta/beta ratio and behavioral inhibition, such that people with high theta/beta ratios are more impulsive and tend to take higher risks. This idea is all the more interesting since increased theta/beta ratio and theta power are common features of attention-deficit/hyperactivity disorder (ADHD; Clarke et al, 2002b, di Michele et al, 2005, Snyder and Hall, 2006, a condition that is characterized by impulsivity and risk taking (Ernst et al, 2003, Masunami et al, 2009, Sonuga-Barke et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that high theta/beta ratio mainly reflects increased power in the theta band (di Michele, Prichep et al 2005;Snyder and Hall, 2006). Rodent studies show that theta EEG is generated for a large part in the septo-hippocampal system (Vertes and Kocsis, 1997).…”
Section: Introductionmentioning
confidence: 99%